Proposed contract manufacturing strategy for Baby Food Industry using Kepner-Tregoe and Analytic Hierarchy Process (AHP) Approach - Dhenok Puspita Zahara; Gatot Yudoko (International Journal of Accounting and Management Information Systems, 2024)
Purpose: This study aims to determine the most appropriate contract manufacturing strategy for PT. SA to ensure sustainable fulfillment of its MA baby food products, amidst regulatory changes and operational risks from overseas production. Methods: A mixed-method approach was employed, integrating qualitative methods (interviews and FGDs with Subject Matter Experts using Kepner-Tregoe and Why Tree analysis) and quantitative techniques through the Analytic Hierarchy Process (AHP). The criteria used for decision-making included cost, schedule, delivery, capacity, capability, and quality. Results: The AHP analysis identified schedule (32.95%) and cost (30.31%) as the most influential criteria. For short-term resolution, the strategy “Produce in existing contract manufacturing and distribute using a 3rd party trader” scored the highest (49.56%). For long-term sustainability, “Terminate existing manufacturing and produce in alternative local contract manufacturers in Indonesia” was the optimal choice (31.55%). Conclusion: Selecting the right strategy helps mitigate sales loss risk (up to IDR 97 billion annually), ensures product availability, and aligns with government import restrictions. Each alternative was evaluated for feasibility, risks, and potential savings. Limitation: This study is specific to PT. SA’s baby food segment and may not fully generalize to other industries or products with different supply chain dynamics or regulatory constraints. Contribution: The study contributes a structured decision-making model using Kepner-Tregoe and AHP to optimize contract manufacturing strategies, supporting firms in navigating supply chain disruptions under regulatory pressure.